Pengaruh Media Komunikasi Whatsapp terhadap Media Kebutuhan Afiliasi Mahasiswa STP Don Bosco Tomohon - Jearne Felix Imbang; Paulus Joseph Mentang (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
The problem in this study is about the low intensity of student in the WhatsApp group. This affects the need for student affiliation. Many students who rarely open messages in the WhatsApp group. The purpose of this study was to determine the intensity of WhatsApp usage among students at STP Don Bosco Tomohon and to determine the effect of the group. This study used a quantitative method, with 100 students as a population and sample of 80 students. In the calculation, the researcher uses the slovin formula. The instrument used is a questionnaire. Respondents only put a checkmark on the answer they considered correct. Then the researcher will manage the collected data using the IBM SPSS 25 for windows application. Hypothesis Testing 1, the use of the WhatsApp communication medium at STP Don Bosco Tomohon is very good. Hypothesis 2, the need for student affiliation at STP Don Bosco Tomohon is high. The use of the WhatsApp communication medium has quite a 35% influence on the affiliation needs of STP Don Bosco Tomohon students, although the effect is less strong (low) and 65% is influenced by other factors. The intensity of the use of communication media Whatsapp at STP Don Bosco Tomohon is very good, with an R Count coefficient of 0.82, and an R Count coefficient on Student Affiliation Needs in the good category, with a value of 0.73. From the results of this study, based on the results of the correlation analysis that the WhatsApp communication media has a less strong and significant effect on the affiliate needs of STP Don Bosco Tomohon students.